The Economic Well-Being of Older People in International Perspective: A Critical Review - Richard Disney; Edward Whitehouse (Luxembourg Income Study (LIS), 2002)
This paper surveys a dozen international comparative studies of poverty, income distribution and older people in industrialized countries using data up to the mid-1990s. It addresses a series of questions. At what level are the incomes of the elderly relative to the population as a whole? How has this changed over the past two decades? How many of the old are poor? How many of the poor are old? Are the oldest of the old poorer than younger pensioners are? The results show that the incomes of older people are typically around 80 per cent of incomes of the whole population. This ratio has been increasing over the past two decades in most countries. Although there remain pockets of poverty among the elderly, the old are generally represented proportionally or under-represented among the poor.
Keywords: 330; Alte Menschen; Lebensstandard; Armut; Altersvorsorge; Einkommensverteilung; Vergleich; Industrieländer